Effects of Artificial Shading and Plant Density on Corymbia Citriodora Seedling Characteristics - Nardini, Claiton; Sgarbossa, Jaqueline; Mariotto, Axel Bruno; Pretto, Matheus Milani; Elli, Elvis Felipe; Oliveira, Davi de; Schmidt, Denise; Caron, Braulio Otomar (FapUNIFESP (SciELO), 2022)
The objective of this work was to evaluate the influence of colored shade mesh and plant density on the morphological characteristics of Corymbia citriodora seedlings. The highest radiation efficiency was found in the blue mesh, 7.01 g MJ-1 and 5.72 g MJ-1 for average and high density respectively. For dry matter and leaf area index at high density, the treatment without mesh followed by the red mesh was the best. The chlorophyll index did not differ between treatments, with mean values of 206.4, 59.1 and 262.0 for chlorophyll a, b and total, respectively. Using principal component analysis, we found the total variance to be 70%. The use of colored shade mesh and plant density altered the radiation use efficiency and dry matter accumulation. Leaf area index was affected only by plant density. The red mesh resulted in the most similar values to the treatment without mesh
Keywords: Air temperature; Leaf area index; Radiation use efficiency